The Influence of Qur’anic Recitation on the Growth Process of Basil Plants: A Scientific Tafsir Analysis - Sofiana Syajarotin Toyyibah; Abdul Fatah; Muhammad Masruri (JIA (Jurnal Ilmu Agama), 2026)
This article aims to explain and analyze the relationship between the recitation of Qur’anic verses and the physiological response of basil plants. Using an exploratory research type, this article examines the possibility of the influence of Qur’anic recitation on living beings other than humans, while also formulating a Qur’anic concept regarding this phenomenon within the framework of scientific interpretation (tafsir sains). The method used in this research is an experimental method by comparing two basil plant objects, namely one plant that is exposed to the recitation of the Qur’an and another plant that is not exposed to such recitation. The research process was carried out for 15 days, starting from June 3, 2025, until June 17, 2025. The results of the study show that the plant that was recited with Qur’anic verses physiologically had leaves that appeared perfectly wide, with no blackened leaves, no small holes in the leaves, and no leaves that were rotten. In contrast, the basil plant that was not exposed to the recitation of the Qur’an showed poorer conditions, indicated by curved leaves, the appearance of blackened parts of the leaves, and the presence of small holes on the surface of the leaves. These findings indicate that the concept of syifā’ in the Qur’an can be interpreted as a form of healing or remedy for various disturbances, which in the context of this study is reflected in the condition of plant leaves that are wilted, blackened, or damaged so that the plant can grow more healthily and optimally. This article contributes to enriching the body of interdisciplinary studies between Qur’anic studies and science, particularly regarding the possible influence of Qur’anic recitation on living beings other than humans.